2007
DOI: 10.1002/art.23178
|View full text |Cite
|
Sign up to set email alerts
|

Atacicept in patients with rheumatoid arthritis: Results of a multicenter, phase ib, double‐blind, placebo‐controlled, dose‐escalating, single‐ and repeated‐dose study

Abstract: Objective. Atacicept is a recombinant fusion protein that binds and neutralizes B lymphocyte stimulator and a proliferation-inducing ligand. The purpose of this study was to investigate the tolerability, pharmacokinetics, and pharmacodynamics of atacicept treatment in patients with rheumatoid arthritis (RA) and to collect exploratory data on clinical outcomes.Methods. In this multicenter, phase Ib, randomized, placebo-controlled, dose-escalating trial, 73 patients were enrolled into 6 escalating-dose cohorts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
140
1
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 198 publications
(154 citation statements)
references
References 22 publications
8
140
1
5
Order By: Relevance
“…Previous studies in RA have indicated that levels of APRIL and BLyS are elevated in synovial fluid relative to serum and have identified both antibody-secreting plasma cells and APRIL-secreting cells within the RA synovium (39,40), suggesting that local inhibition of autoimmune responses may be required for clinical effects. Phase I studies of atacicept in patients with RA have demonstrated that atacicept does enter the synovial compartment and form complexes with BLyS (26,41). However, these observations were made in very small numbers of patients, and whereas one study demonstrated lower levels of atacicept in the synovial fluid than in the circulation (26), the other showed local and systemic levels to be comparable (41).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies in RA have indicated that levels of APRIL and BLyS are elevated in synovial fluid relative to serum and have identified both antibody-secreting plasma cells and APRIL-secreting cells within the RA synovium (39,40), suggesting that local inhibition of autoimmune responses may be required for clinical effects. Phase I studies of atacicept in patients with RA have demonstrated that atacicept does enter the synovial compartment and form complexes with BLyS (26,41). However, these observations were made in very small numbers of patients, and whereas one study demonstrated lower levels of atacicept in the synovial fluid than in the circulation (26), the other showed local and systemic levels to be comparable (41).…”
Section: Discussionmentioning
confidence: 99%
“…Phase I studies of atacicept in patients with RA have demonstrated that atacicept does enter the synovial compartment and form complexes with BLyS (26,41). However, these observations were made in very small numbers of patients, and whereas one study demonstrated lower levels of atacicept in the synovial fluid than in the circulation (26), the other showed local and systemic levels to be comparable (41). Nevertheless, the possibility that atacicept may affect cells in the synovial compartment to a lesser extent than it affects those in the periphery cannot be excluded at this stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of autoimmune-prone lupus mice with Atacicept resulted in delays in the development of proteinuria and increased survival (49). Initial human trials with Atacicept have demonstrated remarkable declines in total serum immunoglobulin levels: in patients treated with Atacicept every 2 weeks for 12 weeks, reductions were seen out to the endpoint at day 85, and median IgG values were reduced by 21%, IgA values by 37% and IgM values by 54% compared to baseline values (50). This is about double the reduction seen in Belimumabtreated patients, (IgG 10%, IgA 14%, IgM 29%, after Belimumab treatment iv at days 0, 14, 28 and every 28 days to 52 weeks along with standard of care, and then analysis at week 52).…”
Section: Introductionmentioning
confidence: 99%